Pengaruh Sosial Media Marketing, E-Wom dan Kualitas Pelayanan pada Keputusan Pembelian di Perusahaan Investasi - Fitriyani Fitriyani (Universitas Prasetiya Mulya, 2023)
This study aims to analyze the effect of social media marketing, electronic word of mouth and service quality on purchasing decisions at GKInvest. The object of research at PT GKInves is a private company engaged in investment and capital markets. The population in this research is 300 investors in GKInvest. The sample distributed was 220 investors, calculated based on the Hair et.al formula (2016) where the sample size is guided by 5 – 10 times the parameter, which is 44 indicators multiplied by 5 (44 x 5). The data collection method uses a survey method, with the research instrument being a questionnaire and then distributing it to each respondent via email. Methods of data analysis using Partial Least Square. The stages of testing include outer model testing, inner model testing and hypothesis testing. This study proves that the variable Social Media Marketing has a positive and significant effect on purchasing decisions, Electronic Word of Mouth has a positive and significant effect on purchasing decisions and Service Quality has a positive and significant effect on purchasing decisions at GKIvest.